Juvenile–adult tree associations in a continental Mediterranean ecosystem: no evidence for sustained and general facilitation at increased aridity - Granda, Elena; Escudero, Adrián; de la Cruz, Marcelino; Valladares, Fernando (Journal of Vegetation Science, 2012)
Question How do tree species identity, microhabitat and water availability affect inter- and intra-specific interactions between juvenile and adult woody plants? Location Continental Mediterranean forests in Alto Tajo Natural Park, Guadalajara, Spain. Methods A total of 2066 juveniles and adults of four co-occurring tree species were mapped in 17 plots. The frequency of juveniles at different microhabitats and water availability levels was analysed using log-linear models. We used nearest-neighbour contingency table analysis of spatial segregation and J-functions to describe the spatial patterns. Results We found a complex spatial pattern that varied according to species identity and microhabitat. Recruitment was more frequent in gaps for Quercus ilex, while the other three species recruited preferentially under shrubs or trees depending on the water availability level. Juveniles were not spatially associated to conspecific adults, experiencing segregation from them in many cases. Spatial associations, both positive and negative, were more common at higher water availability levels. Conclusions Our results do not agree with expectations from the stress-gradient hypothesis, suggesting that positive interactions do not increase in importance with increasing aridity in the study ecosystem. Regeneration patterns are species-specific and depend on microhabitat characteristics and dispersal strategies. In general, juveniles do not look for conspecific adult protection. This work contributes to the understanding of species co-existence, proving the importance of considering a multispecies approach at several plots to overcome limitations of simple pair-wise comparisons in a limited number of sites.
Keywords: faginea; Juniperus thurifera; patterns; Pinus nigra; Quercus; Quercus faginea; Quercus ilex; Regeneration; spatial; spatial patterns; Stress-gradient hypothesis; water; Water availability

Asociación espacial de especies leñosas dominantes a lo largo de gradientes ambientales: estudio de la regeneración de un bosque mediterráneo continental - Granda, Elena; Valladares, Fernando; Escudero, Adrián; de la Cruz, Marcelino; Gimeno, Teresa E; Matesanz, Silvia; Pías, Beatriz; López, David (V Congreso Forestal Español, 2009)
Los fenómenos de competencia y facilitación entre plantas presentan importantes variaciones según la etapa de vida y fisiología de las especies que interactúan, dependiendo además del estrés abiótico e interacciones indirectas. Dada la importancia del análisis espacial en el entendimiento de la estructura y funcionamiento de los ecosistemas, hemos llevado a cabo un estudio descriptivo en localidades contrastadas de bosque mediterráneo continental en el Parque Natural del Alto Tajo (Guadalajara). Se ha registrado el clima de cada localidad y los patrones espaciales de individuos de las cuatro especies dominantes (Quercus ilex subsp. ballota, Quercus faginea, Pinus nigra subsp. salzmannii y Juniperus thurifera). Los propósitos son: determinar patrones de agregación, repulsión o distribución al azar; establecer si dicha distribución está relacionada espacialmente con las características de cada localidad e identificar si los patrones muestran diferencias entre especies. Los resultados indican grandes diferencias entre las cuatro especies. Encontramos que en conjunto, la frecuencia de juveniles era mayor bajo la protección de otros individuos, existiendo diferencias según las especies beneficiarias y benefactoras, y tipo de bosque considerado. Las explicaciones varían desde la facilitación mediada por la mejora en las condiciones microclimáticas hasta una interacción positiva debida al efecto percha o protección frente a los herbívoros. Se discuten las implicaciones de estos resultados para la regeneración natural.
Keywords: Interacciones; Juniperus thurifera L.; Pinus nigra J.F.Arnold subsp. salzmannii (Dunal) F; Quercus faginea Lam.; Quercus ilex subsp. ballota (Desf) Samp.; reclutamiento